Las marcas notorias en el Ecuador y su uso abusivo. - Santafé Santana, Jenny Gabriela (2023)
The rise of commerce has encouraged the creation of numerous new companies and ventures in Ecuador. In this context, branding has emerged as a pivotal element in the economic and commercial development of businessmen and entrepreneurs. Among the myriad distinctive brands, one encounters a critical legal dimension related to copyright, trademark law, industry, and commerce. This research, titled “Famous trademarks in Ecuador and their overuse,” constitutes a legal-doctrinal study with the objective of elucidating the legal actions available to owners of well-known trademarks when faced with unauthorized trademark usage. Consequently, the regulations within the Ecuadorian legal system, international legal instruments, and established legal doctrine exert significant influence. To carry out this analysis, I combined research many methods including the inductive, legal-doctrinal, legal-analytical, and descriptive-legal methods, resulting in a mixed approach. The research encompassed both experimental and non-experimental dimensions, characterized as dogmatic, bibliographic, descriptive legal, and in situ. The study’s target population comprised entrepreneurs registered on the Guayaquil Entrepreneurship Centre, who were surveyed using ten dichotomous questions. The findings of this study underscore a notable lack of awareness among owners of enterprises in the city of Guayaquil regarding the legal ramifications and sanctions associated with arbitrary use of prestigious trademarks. The illicit utilization of these trademarks carries substantial legal and economic consequences for their owners. In light of these findings, it is evident that the arbitrary use of well-known trademarks often stems from a failure to register them, emphasizing the importance of trademark registration.